Tree diversity and their fruiting attributes in periurban Bangalore University Campus - Nagaraja, BC; Prasanna Kumar, CN; Vidyashree, S (Indian Forester, 2020)
The ongoing urbanization around Bangalore reduces green cover, natural forest, wetlands and other ecosystem. The peri-urban biopark of Jnanabharathi campus was studied by laying five transacts of 500 m x 20 m each. Wherein all the woody trees species were identified and their DBH >10 cm were recorded. A total of 1953 woody individuals belonging to 134 tree species and 39 families were recorded in five hectare area of Bio-park, of which 97 belong to native and 41 to exotic species respectively. Fabaceae was the most abundant family followed by Santalaceae and Sapindaceae. Santalum album with 158 individuals was the dominant species followed by Acacia catechu, and Acacia leucophloea. Diversity indices indicate that species richness of the study area is comparable with nearby natural forest. A total of 51 tree species bearing fleshy edible fruits indicates that they provide fruits to variety of wildlife of the campus. This study provides baseline information on the species diversity, composition and fruiting attributes of Jnanabharathi campus.